(untitled) (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
The fundamental question to clarify the identification of millions of individuals brought from sub-Saharan Africa into slavery in Brazil, over three consecutive centuries, is touted in the absence of official documentation of the transatlantic slave trade, which we know to have been destroyed, as well as testimonies others about the ethnic origin of the mass enslaved at the time.